1984
DOI: 10.3109/00207458408990682
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Synaptic Excitability of the Dorsal Lateral Geniculate Nucleus in the Rat

Abstract: Excitability changes of the dorsal lateral geniculate nucleus were recorded in male albino rats (Wistar strain) with chronically implanted electrodes. Both averaged postsynaptic and presynaptic evoked responses showed clear circadian rhythms under a constant dark condition. The circadian rhythmicity of the evoked responses was not as a result of motor activity or due to the sleep-wakefulness changes which might show circadian rhythms independently. Circadian rhythms of antidromic and orthodromic evoked respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Hanada and Kawamura reported circadian rhythms in rat visual circuits in vivo that were independent of vigilance state and abolished by SCN lesions [67]. In this study, lateral geniculate nucleus and optic tract responses to stimulation were consistently higher in the dark phase.…”
Section: Circadian Influences On Synaptic Plasticitysupporting
confidence: 61%
“…Hanada and Kawamura reported circadian rhythms in rat visual circuits in vivo that were independent of vigilance state and abolished by SCN lesions [67]. In this study, lateral geniculate nucleus and optic tract responses to stimulation were consistently higher in the dark phase.…”
Section: Circadian Influences On Synaptic Plasticitysupporting
confidence: 61%
“…A clear connection between discharge strength, the pattern of thalamic neurons, and the state of arousal has been established 25 , 75 , 76 . Moreover, circadian modulation of visual sensitivity and light-induced responses in the DLG, dependent on the suprachiasmatic nuclei, have been described 32 , 77 . As its best-known function, the orexinergic system is sensitive to arousal and mediates its effects by activating various thalamic and cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these direct effects of melatonin on photoreceptive or retinorecipient structures, photic sensitivity may be modulated indirectly as well. For example, the SCN has been implicated in the regulation of a rhythm of excitability in the dorsal lateral geniculate nucleus (Hanada and Kawamura, 1984). Further, Reuss and Kiefer (1989) have reported that following intravenous injections of melatonin, the spontaneous discharge rate of single cells in the cat striate cortex was reduced and the amplitude of responses to photic stimulation was augmented.…”
Section: Discussionmentioning
confidence: 99%